2018
DOI: 10.18203/2349-3291.ijcp20181509
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding dengue infection among parents of children hospitalized for dengue fever

Abstract: Background: Dengue fever is a rapidly emergent infection and is one of the leading causes of hospitalization and health care burden in India. Dengue vectors, human knowledge and behavior have each been reported to play an important role in the transmission of the disease. This study is aimed at assessing the knowledge regarding dengue fever, its transmission, identification of the disease and its complications and its preventive measures among the parents.Methods: This is a hospital based cross sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…More than half of the parents in this study had a positive attitude toward DI prevention and HSB. This mirrors a cross-sectional study conducted in India in 2018 [16] and may result from a similar methodology: surveying a healthcare setting among parents. Participants present in a healthcare setting may already be inclined to have a positive attitude towards DI prevention and HSB.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…More than half of the parents in this study had a positive attitude toward DI prevention and HSB. This mirrors a cross-sectional study conducted in India in 2018 [16] and may result from a similar methodology: surveying a healthcare setting among parents. Participants present in a healthcare setting may already be inclined to have a positive attitude towards DI prevention and HSB.…”
Section: Discussionsupporting
confidence: 60%
“…Thus, parents may have been sensitized to the information, unlike during other studies in the Caribbean [4,9]. Parents were, however, unfamiliar with symptoms of severe DI in children, including abdominal pain, bleeding from the gums, and passing blood with stool, as seen in many KAP studies among parents [2,16,17]. These symptoms are used to distinguish DI from other infections [18], and parents who recognize these symptoms are more likely to associate it with the severity of the disease, as demonstrated in a cross-sectional study among Malaysian parents [2].…”
Section: Discussionmentioning
confidence: 99%
“…Sources of information can influence the formation of a positive behavior that is owned by someone. Research conducted by (Harish et al, 2018) The results showed that the most sources of information were obtained from the media in the form of television (89%), radio (41%) and newspapers (33%). Television is a medium that plays a very big role in making people aware of DHF and its prevention.…”
Section: Resultsmentioning
confidence: 99%
“…According to [42], it has been previously stated that the most common contributing factor to the emergence and spread of infectious disease agents has to do with the changes of habitats such as irrigation systems, wetland, deforestation, road building, and natural resources, flow of water bodies rich in nutrients as well as the ability to with stand any chance that may occur in a given habitat, as far as such habitat can support the development and abundance of mosquitoes [44,45]. Equally every habitat possesses specific ecological properties that are important to the fate of anti-larval biological control strategies aimed at reducing juvenile mosquito populations they support [46].…”
Section: Discussionmentioning
confidence: 99%